2021
DOI: 10.1016/j.heliyon.2021.e06284
|View full text |Cite
|
Sign up to set email alerts
|

Exploring existing drugs: proposing potential compounds in the treatment of COVID-19

Abstract: The COVID-19 situation had escalated into an unprecedented global crisis in just a few weeks. On the 30 th of January 2020, World Health Organization officially declared the COVID-19 epidemic as a public health emergency of international concern. The confirmed cases were reported to exceed 105,856,046 globally, with the death toll of above 2,311,048, according to the dashboard from Johns Hopkins University on the 7 th of February, 2021, though the actual figures may be much higher. Conserved regions of the Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…This is one of the most significant impasses to significantly reduce the number of deaths from this virus (Kostarelos 2020 ). The simplest and quickest way to establish a drug for the treatment of COVID-19 is from drug repurposing, which consists of giving new uses to drugs already approved for other diseases (Kabir et al 2021 ).…”
Section: Overview Of Nanotechnology Products For Covid-19mentioning
confidence: 99%
“…This is one of the most significant impasses to significantly reduce the number of deaths from this virus (Kostarelos 2020 ). The simplest and quickest way to establish a drug for the treatment of COVID-19 is from drug repurposing, which consists of giving new uses to drugs already approved for other diseases (Kabir et al 2021 ).…”
Section: Overview Of Nanotechnology Products For Covid-19mentioning
confidence: 99%
“…The RBD of the spike protein is an often-used target in order to inhibit its interaction with hACE2 receptors, thereby preventing viral infection. Many studies have identified potential inhibitors using molecular docking and/or molecular dynamics (MD) simulations against solely the RBD (Faheem et al, 2020;Prajapat et al, 2020;Trezza et al, 2020;Kumar et al, 2021;Hu et al, 2022;Wu et al, 2022) or solely the hACE2 receptor (Benítez-Cardoza and Vique-Sánchez, 2020; Kabir et al, 2021). Very few studies have analyzed the interaction of small drug-like molecules with the RBD-hACE2 interface.…”
Section: Introductionmentioning
confidence: 99%
“…So the whole procedure becomes time-consuming and expensive with a high possibility of failure. So as an alternative, another novel approach to identify new therapeutic option is drug repurposing 10 , 11 . Drug repositioning is the main activity of drug repurposing which involves the investigation of new therapeutic indications of existing drugs.…”
Section: Introductionmentioning
confidence: 99%